PENGARUH QUENCHING SETELAH PENGELASAN TERHADAP KOROSI DI BAWAH INSULASI MEDIA AIR LAUT PADA BAJA A36 - Ridho, Arda Roshid (Pt. Anagata Sembagi Education, 2024)
Corrosion in low-carbon steel is a significant issue in the industrial world, particularly in the oil, gas, refining, and chemical industries, as it leads to substantial financial losses. The total losses experienced by companies in Indonesia are estimated to reach 2-5% of the country's GDP. Corrosion arising from insulation damage, known as Corrosion Under Insulation (CUI), is challenging to detect but has a profound impact on industrial processes. Welding quality and corrosion resistance can be improved through post-weld heat treatment (PWHT). This research aims to investigate the influence of rapid cooling after welding low-carbon ASTM A36 steel on corrosion events under insulation using the